Kajian Relevansi Sifat Piskokimia Tanah pada Kualitas dan Produktivitas Kentang (Solanum Tuberosum L) - Arsa, I Wayan; Setiyo, Yohanes; Nada, I Made (Jurnal BETA (Biosistem dan Teknik Pertanian), 2013)
This research  was conducted to determine the effect level of NPK fertilizer added with compost fertilizer on soil psychochemical properties, the quality and the productivity of Granola G4 potatoes. This study lesed Split plot with : two sub plot, and four level doses NPK fertilizer. Each level of NPK fertilizing was repeated three times. NPK fertilizing levels are: 160 kg / ha (P1), 180 kg / ha (P2), 200 kg / ha (P3), and 220 kg / ha (P4), with chicken manure from compost. Dose of compost was  20 tonnes per hectare. Variable of this research were : soil structure, soil water holding capacity, permanent wilting point of crops, crops water availability, pH, soil organic matter, productivity and quality of petetues. Availability of water crops was between    21 – 24 % wet basis (w.b).  Each level of NPK fertilization was able to change pH from 6.5 to 6.9.  Content of C-organic content at early potatoes planting was  4.0 – 4.1 % and after potatoes harvesting the C-organic content was 4.7 – 6.4 %. The potatoes productivity at NPK fertilization 200 tones/ha and 220 tones/ha was 30 tones/ha. The number of tubers can be used as seed was 38.4% and 36.5% with the number of tubers rot was 3.8 and 3.6%
Keywords: Potatoes, soil phycochemical, doses, productivity and quality.